2018
DOI: 10.1007/s10803-018-3663-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Individual Differences in Cognitive, Affective, and Spontaneous Theory of Mind Among School-Aged Children with Autism Spectrum Disorder

Abstract: The present study examined individual differences in theory of mind (ToM) among a group of 60 children (7-11 years-old) with autism spectrum disorder (ASD) and average intelligence. Using open-ended and structured tasks to measure affective ToM, cognitive ToM, and spontaneous social attribution, we explored the nature of ToM and assessed whether ToM predicts the phenotypic heterogeneity in ASD through structural equation modeling. Affective ToM uniquely predicted social symptom severity, whereas no ToM types p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 57 publications
0
33
0
11
Order By: Relevance
“…Previous studies concluded that, although performance on ToM tasks is associated with different subtypes of prosocial behavior (helping, cooperating, and comforting), the magnitude of the association is relatively weak (Imuta et al, 2016). Moreover, no ToM types have predicted parent reported social functioning of their children with ASD (Altschuler et al, 2018), and no simple or direct relationship has been found between behavioral indices of ToM ability and everyday social interactions, as in friendships described by children with high-functioning ASD (Calder et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies concluded that, although performance on ToM tasks is associated with different subtypes of prosocial behavior (helping, cooperating, and comforting), the magnitude of the association is relatively weak (Imuta et al, 2016). Moreover, no ToM types have predicted parent reported social functioning of their children with ASD (Altschuler et al, 2018), and no simple or direct relationship has been found between behavioral indices of ToM ability and everyday social interactions, as in friendships described by children with high-functioning ASD (Calder et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, they concluded that the ability to understand emotions and beliefs is necessary in order to display appropriate social behavior. Finally, Altschuler et al (2018) reported a positive relationship between affective ToM (ability to infer other people's emotions) and social symptoms characteristic of ASD. In other words, affective ToM predicted the severity of social symptoms, but not social functioning in a broad sense.…”
Section: Tom and Adaptive/social Skillsmentioning
confidence: 98%
“…Klin called the measure he developed the Social Attribution Task (SAT), and it has since been used in follow-up studies with individuals diagnosed with ASD (Klin & Jones, 2006) and schizophrenia (Bell, Fiszdon, Greig, & Wexler, 2010). More recently, researchers have developed a multiplechoice version of the SAT (SAT-MC) which provides scores that correlate positively with measures of adaptive functioning (Burger-Caplan, Saulnier, Jones, & Klin, 2016) and other ToM tasks (Altschuler et al, 2018).…”
Section: Recent Applications Of Heider and Simmel's Methodsmentioning
confidence: 99%
“…The current literature on individual differences in ToM ability is limited, and what does exist is largely siloed into subfields such as developmental or clinical psychology. A large portion of such work focuses on variations in the development of ToM among children (e.g., Bowman et al, 2017;Devine & Hughes, 2013;Wang et al, 2016) using false-belief tasks that do not capture the full complexity of ToM (Altschuler et al, 2018;Apperly, 2012;Tager-Flusberg, 2011). Much of the remaining research focuses on ToM deficits in those with mental illness or developmental disabilities (Baron-Cohen et al, 1985;Pedersen et al, 2012), but such studies are often limited in their sample size and methods of assessing ToM ability.…”
Section: Differences In Agreeableness and Social Cognitive Abilitymentioning
confidence: 99%